Old Age in Arab American Literature: A Reading of Frances Khirallah Noble’s and Joseph Geha’s Short Stories - Gláucia Renate Gonçalves; Letícia Malloy (Ilha do Desterro, 2025)
This essay[1] aims at examining old age in short stories by the Arab American writer Frances Khirallah Noble (2000) and the Lebanese writer Joseph Geha (1990). For such, it takes into account the Arab migration to the United States in the first decades of the twentieth century. Moreover, it discusses the dualism between disseminating and reinforcing traditional practices from the place of origin and, on the other hand, a tendency toward assimilation as the way to a successful settlement in the new country. As portrayed by the analyzed literary texts, the tension between perpetuating traditions and embracing foreign traits directly affects elder members of Arab American communities, who may be either pushed to the margin by younger generations or respected for holding a set of values and memories which can be used for the benefit of their communities.